FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PEMILIHAN METODE KONTRASEPSI JANGKA PANJANG OLEH PASANGAN USIA SUBUR - Herniyatun, Herniyatun; Zakiah, Siti; Safrina, Safrina; Noorma, Nilam; Sianipar, Kandace (Ensiklopedia of Journal, 2024)
Abstract: According to Indonesian population data, the population growth rate in Indonesia is still relatively high. Therefore, one of the efforts made by the government in dealing with increased population growth is to promote the use of contraceptives. Contraceptives recommended by the government are long-term contraceptive methods (MKJP), but the coverage of MKJP use is still low, which is around 19.8%. The low use of MHJP is feared to cause maternal and child health problems. The purpose of the study was to determine the factors associated with the selection of long-term contraceptive methods by couples of childbearing age. This study is a quantitative study that is analytic in nature with a cross-sectional research design and a sample size of 106 PUS with the sampling technique used is simple random sampling. Data analysis was performed by univariate analysis and bivariate analysis with chi-square test and PR value. The results showed there was a relationship between knowledge (p value: 0.000), socioeconomics (p value: 0.041) and partner support (p value: 0.033). It is recommended that the Paal X puskesmas provide complete contraceptives so as to provide opportunities for acceptors to use contraceptives that are in accordance with their physical and health conditions and it is recommended that PUS can play an active role in every family planning activity, routinely consult with family planning service officers, and are expected to independently seek information.Keywords: Spousal Support, Knowledge, Socioeconomics.